Efektivitas Pemasaran KBIHU Berdasarkan Perspektif Jamaah (Studi Komparatif Pada KBIHU Zamzam dan KBIHU Thoriqul Jannah) - Amaruddin, Amin Awal; Islachiyana, Rifda (MARGIN ECO, 2024)
This research was conducted to find out the effectiveness of the marketing strategy of KBIHU Zamzam and KBIUH Thoriqul Jannah based on the Jamaah perspective. The research method used is quantitative. Data is collected through the dissemination of questionnaires to the KBIHU community in the form of closed questions using the Likert Scale to 30 respondents in each KBIHO. Quantitative data is analyzed using descriptive statistical analysis. The results of the research show that, based on the theory of marketing effectiveness presented by Theodore Levitt, the average cumulative score for KBIHU Zamzam is 4.31, whereas KBIUH Thoriqul Jannah reaches 4.26, both of which belong to the category "very effective". These criteria relate to the marketing efficiency from the Jamaah perspective in KBIHO Zamzam and KBIHA ThoriQL Janná, so it can be concluded that the marketing efficacy has been achieved overall.